Filling the gap: Open economy considerations for more reliable potential output estimates - Zsolt M. Darvas; András Simon (Bruegel, 2015)
This paper argues that the Phillips curve relationship is not sufficient to trace back the output gap, because the effect of excess demand is not symmetric across tradeable and non-tradeable sectors. In the non-tradeable sector, excess demand creates excess employment and inflation via the Phillips curve, while in the tradeable sector much of the excess demand is absorbed by the trade balance. We set up an unobserved-components model including both a Phillips curve and a current account equation to estimate 'sustainable output' for 45 countries. Our estimates for many countries differ substantially from the potential output estimates of the European Commission, IMF and OECD. [...]
Keywords: C32; E32; F41; 330; equilibrium current account; international trade; Kalman-filter; open economy; Phillips-curve; potential outpu; real-time data; sustainable output; state-space models